Immune modulatory effects of radiotherapy as basis for well-reasoned radioimmunotherapies - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Hecht, Markus; Gaipl, Udo; Deloch, Lisa (Strahlentherapie und Onkologie, 2018)
BACKGROUND: Radiotherapy (RT) has been known for decades as a local treatment modality for malign and benign disease. In order to efficiently exploit the therapeutic potential of RT, an understanding of the immune modulatory properties of ionizing radiation is mandatory. These should be used for improvement of radioimmunotherapies for cancer in particular. METHODS: We here summarize the latest research and review articles about immune modulatory properties of RT, with focus on radiation dose and on combination of RT with selected immunotherapies. Based on the knowledge of the manifold immune mechanisms that are triggered by RT, thought-provoking impulse for multimodal radioimmunotherapies is provided. RESULTS: It has become obvious that ionizing radiation induces various forms of cell death and associated processes via DNA damage initiation and triggering of cellular stress responses. Immunogenic cell death (ICD) is of special interest since it activates the immune system via release of danger signals and via direct activation of immune cells. While RT with higher single doses in particular induces ICD, RT with a lower dose is mainly responsible for immune cell recruitment and for attenuation of an existing inflammation. The counteracting immunosuppression emanating from tumor cells can be overcome by combining RT with selected immunotherapies such as immune checkpoint inhibition, TGF-β inhibitors, and boosting of immunity with vaccination. CONCLUSION: In order to exploit the full power of RT and thereby develop efficient radioimmunotherapies, the dose per fraction used in RT protocols, the fractionation, the quality, and the quantity of certain immunotherapies need to be qualitatively and chronologically well-matched to the individual immune status of the patient.
EVALuna2:36465